Role of yoga and meditation on serum DHEAS level in first year medical students - Kumar, Kislay; Kumar, Devesh; Singh, Vinay; Pandey, Pooja T.; ., Divya (International Journal of Research in Medical Sciences, 2018)
Background: Dehydroepiandrosterone sulfate (DHEAS), secreted by adrenal cortex, acts in the human body as a neurosteroid, cardio-protective, anti-diabetic, anti-obesity and immune-enhancing agent. It is also reported as a youth hormone. But due to various stimulators of stress, and also as an antagonist of cortisol, DHEAS level decreases. Yoga and meditation regulates the level of hormones and neurotransmitters that affect physiological function. Methods: This study was performed on 1st yr. medical students whose DHEAS level was low due to acute stress. 55 medical students were selected as participants through counseling and were divided into Yoga group (n= 27) and control group (n=28). Their morning serum DHEAS level was assessed and yoga group were instructed to practice Yoga (1hr/day for 12 weeks) under supervision of Yoga instructor. No such instruction was given to control group. Results: As a marker of youth and immunity, increase in DHEAS level decreases susceptibility to infections, reduces aging process as well as improves other functions. Yoga and meditation is documented to increase DHEAS level in regular practitioners. Statistical analysis has shown an increase in morning S. DHEAS level in yoga practitioners. Pre-study and post study values were 3.5±2.48 and 3.61±1.73 respectively in yoga group (overall 3.1% increase, P Value = 0.025, significant at 0.05) whereas 3.36±1.98 and 2.58±1.49 respectively in control group (23.2% decrease, P Value =0.84, not significant). Conclusions: This study concludes that practicing Yoga has significantly raised S. DHEAS level in medical students and improved their immunological status as well as enhances mood and behavior.